Scenical Representation and Acrobatic Performance The Forces of Love and Magic - Bolognesi, Mario [UNESP] (Univ Estado Santa Catarina-udesc, 2019)
In 1678, Saint-Germain's fair received the show The Forces of Love and Magic. The company Atard-Maurice was responsible for the staging that added acrobatics acts, rope balance, dancing and comedy. The spetacte has characteristics that will be present in the operacomic, the creation of the Fair Theater, and in the theater shows of attractions.
Keywords: Fair Theater; Montage of Attractions; Alard; Vondrebeck